CD36 Polymorphism (rs1761667) Was Associated with Fatty Liver in a Japanese Population. (29th May 2020) - Fujii, Ryosuke; Ichino, Naohiro; Osakabe, Keisuke; Sugimoto, Keiko; Yamada, Hiroya; Ando, Yoshitaka; Hishida, Asahi; Wakai, Kenji; Suzuki, Koji; Kondo, Takaaki
Abstract: Objectives: Nonalcohol fatty liver disease (NAFLD) is one of the considerable health problems in the world. NAFLD is a representative phenotype in the liver reflecting individual's lifestyle. Previous studies suggested that a single nucleotide polymorphism (SNP) in the CD36 gene was associated with dietary fat intake and fat metabolism. Therefore, we hypothesized that this SNP may be associated with fatty liver (FL) and NAFLD. We conducted this cross-sectional study to examine the association between two CD36 polymorphisms (rs1761667 and rs1527483) and FL and NAFLD in a Japanese population. Methods: A total of 525 local residents participated in the health check-up in Yakumo town, Hokkaido, Japan. This cross-sectional study was conducted based on clinical information collected in this health check-up. Among all participants, 57 people were excluded due to the inadequate informed consent, clinical history of liver disease. Genotyping of two polymorphisms in the CD36 gpgbrkkene was performed by using the PCR-CTPP method. Ultrasound examination was performed by four qualified ultrasonographers. In this present, NAFLD was defined as 1) presence of FL and 2) a daily alcohol consumption <10 g in women and <20 g in men. Multivariable regression analysis was performed after adjusting for age, sex, waist circumference, medicine for dyslipidemia. Results: The mean age of participants was 63.4 (10.0). The minor allele frequency of rs1761667 and rs1527483 was 0.26 and 0.21, respectively. The presence of FL and NAFLD was 90 (19.2%) and 67 (14.3%), respectively. Multiple regression analyses showed a significant association between rs1761667 and presence of FL ( P = 0.04), and FL grade ( P = 0.03). However, rs1761667 was not significantly associated with NAFLD ( P = 0.11). No significant associations were found between rs1527483 and FL and NAFLD. Conclusions: A polymorphism (rs1761667) in the CD36 gene was associated with the presence of FL, but we did not find a significant association between this SNP and NAFLD. Funding Sources: This study was supported by the Mishima Kaiun Memorial Foundation.